HUKUMAN HADD PELAKU ZINA: ANALISIS TAFSIR KLASIK DAN KONTEMPORER SURAT AN-NUR AYAT 1-3 - Aisy, Mafaza Rohadatul; Imawan, Dzulkifli Hadi (IAIN Ambon, 2025)
This study examines the hadd punishment for adultery through an interpretive analysis of the Qur'an Q.S An-Nur verses 1-3 and the hadith, and makes a comparison with Article 284 of the Criminal Code (KUHP) from the perspective of Indonesian law. This study uses a qualitative approach, with a library research method. This study uses primary sources: classical tafsir books by Ali Al-Shabuni, Wahbah Zuhaily, Al-Qurthubi, and other commentators. Supporting data were obtained from a review of relevant academic books and journals. The results of the study indicate that Islamic law views adultery as a serious violation that is categorized based on the perpetrator's marital status, namely ghairu muhshan (unmarried) and muhshan (married), with different legal implications. In this regard, there is an overlap between Islamic criminal law and Indonesian positive law in viewing adultery, although Islamic law offers a more comprehensive scope. This study confirms that hadd punishment in Islam is a form of holistic protection of Human Rights, including the rights of other parties. Unequal punishment for human rights violators on the grounds of respecting human rights is a disregard for the principle of human rights itself. Keywords: interpretation, zina, hadd